Algunas referencias sobre el concepto de arqueología en España en el siglo XIX - Berlanga Palomo, Mª José (Gerión. Revista de Historia Antigua, 2003)
In this article i propose to explain the concept of archaeology in this by the Spanish archaeologist in the european context, the evolution of the term and the difficulty to separate archaeology and fine arts.